ANALISIS PENERAPAN KESEHATAN DAN KESELAMATAN KERJA MENGGUNAKAN METODE HAZARD IDENTIFICATION AND RISK ASSESSMENT (HIRA) (STUDI KASUS: UKM ATHAYA DRUMBAND) - Ayudyah Eka Apsari; Anindya Agripina Hadyanawati (Universitas Islam Nahdlatul Ulama Jepara, 2023)
ANALYSIS OF OCCUPATIONAL HEALTH AND SAFETY USING HAZARD IDENTIFICATION AND RISK ASSESSMENT (HIRA)(CASE STUUDY: SME’s ATHAYA DRUMBAND)DIY Province is a province that has a large number of SMEs. The number of SMEs in Yogyakarta in 2019 reached 42,155 units. One sector that is very influential on the economy is an industry engaged in the manufacturing sector. One of the products in the manufacturing sector is drumband equipment. This research was conducted to reduce work accidents by identifying the risks of hazards in the workplace. Identification of work accidents using the Hazard Identification and Risk Assessment (HIRA) method. HIRA aims to identify the potential hazards that exist in a company to assess the magnitude of the chance of an accident or loss. The results of this study state that there are 6 potential hazards in UKM Athaya Drumband. Being exposed to wood chips from cutting results, tired due to work attitudes, being exposed to chemicals, getting burns and impaired vision due to welding activities, and being injured due to exposure to leftover production materials that are scattered. The biggest risk is the welding process, namely the dangerous end of the weld and work attitude with a percentage of 28.57%. The potential hazard in the form of chemicals in paint also has a high presentation of 19.05%.